Evaluation of blast resistance genes Pi9 and Pi54 in rice against local isolates of Tamil Nadu - Thiyagarajan Thulasinathan, Rohit Kambale, Bharathi Ayyenar, S. Manonmani and Raveendran Muthurajan (Electronic Journal of Plant Breeding, 2020)
Rice production system is greatly affected by blast disease caused by Magnaporthe grisea Barr which causes significant yield reduction throughout Asia and different parts of the globe. Developing resistant varieties has been most efficient and economical method for controlling blast disease in rice. Identification of broad spectrum resistance genes against prevailing isolates of the pathogen is a key determining success of developing resistant varieties. However, the blast resistance characterization and evaluation has not been well studied. In the current study, 3 parental lines namely CO 51 (Pi54), 562-4 (a NIL of CO 43 harboring Pi 9) and a susceptible genotype Improved White Ponni (IWP) were evaluated against local isolates of blast pathogen. Presence of Pi9 and Pi54 blast resistance genes in the parental lines was confirmed by using functional markers such as NBS4 and Pi54MAS respectively. All the three genotypes were evaluated against blast disease in a hot spot environment. Both CO51 and 562-4 carrying the Pi54 and Pi9 genes respectively showed moderate resistance against blast disease whereas IWP showed a susceptibility reaction against blast disease. Results indicated that pyramiding of these genes would improve resistance against blast disease. The present study has favored the selection of blast resistant parental lines which can be utilized as donor in breeding programs.